MEMBANGUN BRAND (IMAGE) FAKULTAS DALAM RANGKA MENYONGSONG ERA FOURTH INDUSTRIAL REVOLUTION (4IR) - Nihayatul Maskuroh; Asep Dadan Suganda; Ma'mun Nawawi (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
This study aims to determine how the efforts of the Faculty of Islamic Economics and Business, UIN Sultan Maulana Hasanuddin Banten to build a brand (image) in dealing with the Fourth Industrial Revolution, as well as the potential and opportunities of Faculty. The method of this research used descriptive qualitative by guided interviews were conducted to the stakeholders and faculty users. It can be seen that the the efforts of the Faculty to build the brand (image) in dealing with the Fourth Industrial Revolution through five aspects such; aspects of department accreditation, aspects of student achievement, aspects of graduate quality, aspects of excellent activities, and aspects of relations with alumni. Meanwhile, in order to optimize all the potentials and opportunities to build the brand (image), the Faculty of Islamic Economics and Business will implement an aggressive Grand Strategy with actively optimizing the strength to take advantages of all the opportunities. Furthermore, by carrying out this strategy, hopefully that the Faculty of Islamic Economics and Business have the added value and selling points in dealing with the Fourth Industrial Revolution.